The Role of Sufistic-Based Kiai Leadership in Developing the Character of Santri in the Pesantren - Chusnul Muali; Moh Rofiki; Hasan Baharun; Zamroni Zamroni; Lukman Sholeh (STAI Hubbulwathan Duri, 2021)
This study aims to describe Sufistic-based Kiai leadership's role in shaping Santri character at the Pesantren Nurul Jadid Paiton Probolinggo. This research is a case study qualitative approach, with Kiai as the subject. We collected data using interview, documentation, and observation techniques, then analyzed using reduction techniques, presenting data, and drawing conclusions. The results showed that the Sufistic-based Kiai's leadership had an essential role in fostering the character of the Santri. The study results indicate that the Sufistic-based Kiai leadership has a vital role in promoting the surface of the Santri. Kiai is a person who gives influence in building character with Uswah (Modelling). This study also found that the factors that influence low morale are that Santri has a common understanding of the latest technological developments. In Sufistic-based leadership, there are four things that a leader must possess: 1) The Tawasuth, 2) The nature of I'tidal, 3) The Tawazun, and 4) The Tasamuh.